The information support organization of cars traffic volume using the system of cooperative trains’ groups - Kekish, N. A. (Science and Transport Progress, 2011)
The article is dealt with proposals for information provision for the organization of intra-railway traffic volumes on a system of mutually coordinated group trains. The structure and composition of the module, its features, a list of the functions to be performed are described. The module is also used for storage and processing of statistical data needed in calculating the plan of forming of the group trains.